Comparing intrafamilial child sexual abuse and commercial sexual exploitation of children: A systematic literature review on research methods and consequences. (July 2018) - Selvius, Kelly; Wijkman, Miriam D.S.; Slotboom, Anne-Marie; Hendriks, Jan
Abstract: Context: Child sexual abuse is known to have a major negative impact on its victims' lives. Knowledge on the consequences of commercial sexual exploitation of children (CSEC), however, is still relatively unexplored and therefore treatment cannot be tailored for these victims. Objectives: This review aims to compare research on consequences of CSEC with those of intrafamilial child sexual abuse (ICSA), with particular attention to the research methods that are used. Methods: The search on seven databases resulted in 1698 studies. Out of these studies, eighteen studies matched the inclusion criteria and were therefore included in this review. Fourteen studies focused on ICSA and four on CSEC. Results: The most notable difference in methodologies was the time between the sexual abuse and interviewing of the victims. This led to a variation in focus of consequences. For ICSA, most studies focused on mental health consequences while for CSEC, the majority focused on physical health consequences, in particular sexually transmitted diseases. Conclusions: Further research on consequences of CSEC is greatly needed. Longitudinal research should focus on comparing the presence of various consequences (mental health, physical health, sexual behavior and daily functioning) in victims of CSEC, victims of ICSA and a non-sexually abused control-group. Highlights: There is a lack of research on the impact of sexual exploitation of children. Methodologically, published studies on both victim groups are incomparable. Research on sexual exploitation of children mainly focuses on physical consequences. The focus of consequences within this group of victims should be expanded.